Idiopathic granulomatous mastitis: A case report - Prueksadee, Jenjeera; Boonjunwetwat, Darunee; Chayakulkheeree, Jatuporn (Chulalongkorn Medical Journal, 2023)
Idiopathic granulomatous mastitis is an uncommon benign breast disease diagnosed from exclusion. It mimics malignant breast tumor in terms of clinical and imaging features. We hereby report a case of painful lump in the left breast. Mammograms and ultrasound findings could not exclude malignant mass. Wide excision was performed and the final histopathological diagnosis of granulomatous mastitis was concluded. In conclusion, the clinical and imaging findings of granulomatous mastitis are similar to carcinoma. Tissue diagnosis was very important to distinguish these two entities before starting management and avoiding unnecessary mastectomy.